Beginning acces 2003 VBA - Gosnell, Denise (Wiley Pub, 2004)
What is this book about? Written by an Access programmer with more than 10 years of VBA experience, this is the perfect guide for Access users who are ready to take their databases to the next level, or for programmers who are new to Access or VBA.